Polar adventures : a chapter book - Nichols, Catherine (new york : Scholastics, 2003)
Briefly discusses some of the explorers of the North and South Poles, including Robert Peary, Ernest Shackleton, Matthew Henson, and Donald Macmillan.
Includes bibliographical references (p. 46).
G4
Keywords: Explorers -- Polar regions -- History -- Juvenile literature; Explorers -- Polar regions; Polar regions -- Discovery and exploration -- Juvenile literature; Polar regions -- Discovery and exploration